2020
DOI: 10.1111/odi.13699
|View full text |Cite
|
Sign up to set email alerts
|

Integrating GWAS and eQTL to predict genes and pathways for non‐syndromic cleft lip with or without palate

Abstract: Objective: To explore susceptibility genes and pathways for non-syndromic cleft lip with or without cleft palate (NSCL/P).Materials and methods: Two genome-wide association studies (GWAS) datasets, including 858 NSCL/P cases and 1,248 controls, were integrated with expression quantitative trait loci (eQTL) dataset identified by Genotype-Tissue Expression (GTEx) project in whole-blood samples. The expression of the candidate genes in mouse orofacial development was inquired from FaceBase. Protein-protein intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…We found that many of the genes with increased expression in the hypertrophic region of dorsal lip were already demonstrated to play a role in lip morphogensis and pathobiology in other vertebrates, including alx1 [32], alx3 [33], angptl2 [34], arid3a [35], crip2 [36], ddr2 [37], dpysl2 [38], itga5 [39], lmna [40], mgp [41], rgs5 [42], rhob [42,43], rxfp2 [44], sostdc1 [42,45], thbs3 [46], vcan [47,48], and vtn [49]. Among the transcriptionally repressed genes, we also found candidates with functions which were previously implicated in defective lip morphogenesis in other vertebarates such as cd96 [50], ep300 [51][52], fgfrl1 [53], frzb [54], hectd1 [55,56], mmp13 [49], slc16a6 [57], and syne1 [58].…”
Section: Discussionmentioning
confidence: 84%
“…We found that many of the genes with increased expression in the hypertrophic region of dorsal lip were already demonstrated to play a role in lip morphogensis and pathobiology in other vertebrates, including alx1 [32], alx3 [33], angptl2 [34], arid3a [35], crip2 [36], ddr2 [37], dpysl2 [38], itga5 [39], lmna [40], mgp [41], rgs5 [42], rhob [42,43], rxfp2 [44], sostdc1 [42,45], thbs3 [46], vcan [47,48], and vtn [49]. Among the transcriptionally repressed genes, we also found candidates with functions which were previously implicated in defective lip morphogenesis in other vertebarates such as cd96 [50], ep300 [51][52], fgfrl1 [53], frzb [54], hectd1 [55,56], mmp13 [49], slc16a6 [57], and syne1 [58].…”
Section: Discussionmentioning
confidence: 84%
“…They demonstrated that NSCL/P development could be regulated by genes related to ubiquitin-mediated proteolysis and DNA synthesis, and the fatty acid metabolism pathway. 23 Deubiquitination, described as the removal of ubiquitin from the protein substrate bound by ubiquitin, is mediated by several deubiquitinating enzymes (DUBs), including ubiquitin-specific processing protease (USP). 24 USP17L6P belongs to a subfamily of cytokine-inducible DUBs.…”
Section: Discussionmentioning
confidence: 99%
“…The whole-blood eQTL data was derived from the Genotype-Tissue Expression (GTEx) version 6 database (n = 338) [ 17 ]. The gene expression data was obtained using paired-end RNA-seq (Illumina TruSeq; Illumina Inc) and the genotype data was from whole-genome sequencing.…”
Section: Methodsmentioning
confidence: 99%